Exploration of the Causes of Correspondence Education of Traditional Chinese Medicine in Modern China - Longkui JIANG; Zongming ZHANG (Yixue yu zhexue, 2025)
There are four main reasons for the emergence of correspondence education of Traditional Chinese Medicine(TCM) in modern China. First, correspondence education, with its unique advantages, has become a natural choice for TCM education sector to break through difficulties and seek its own development. The introduction of Western correspondence education model and the shaping of China's modern education system provided a structural reference. The establishment of modern China's postal system and the flourishing printing and publishing industry provided technological support. Adaptations aligning correspondence education with TCM's educational principles ensured its relevance in cultivating medical talent. Although modern correspondence education of TCM has many limitations, it laid the foundation for contemporary TCM distance education and significantly contributed to the development of modern TCM education models in China.